Influence of Crop Density and Weeding Frequency on Crop Growth and Grain Yield in Wheat - M. I., Tariful; A. K., Emran; M. A., Gaffer (Universiti Putra Malaysia Press, 1998)
Influence of seed rates at 100, 125, 150 and 175 kg/ha and four weeding frequencies Wo (no weeding), Wi (weeding after 20 days of sowing), W2 (weeding after 20 and 40 days of sowing) and (weeding after 20, 40 and 60 days of sowing) on growth and yield of wheat were studied. The major weeds species were Chenopodium album L., Cynodon dactylon (L) Pers, Dactyloctenium aegyptium L. and Vicia sativa L. The highest grain yield per hectare, panicle length, and filled grains/panicle were obtained with the seeding rate of 125 kg/ha. The lowest grain yield (3.11 t/ha) with minimum effective tillers/plant, panicle length and filled grains/panicle were produced by the highest seed rate (175 kg/ha). The plant population per meter square was significantly influenced by seed rates. Weeding at 20 and 40 days after sowing (W) gave the highest grain and straw yields along with highest effective tillers/plant, panicle length, and filled grains/panicle. On the other hand no weeding treatment gave the lowest grain and straw yields, effective tillers/plant, panicle length and filled grains/panicle. The critical period of weed competition was between 20 and 40 days after sowing. High seed rate with three times weeding (W) decreased weed dry weight/m2 significantly.